(untitled) (Research, Society and Development, 2025)
This study aims to analyze the scientific evidence regarding the role of dentistry in palliative care, seeking to understand how the literature addresses the most prevalent oral manifestations, interactions developed for symptom relief, and challenges faced by professionals in the field. The articles included, dated between 2020 and 2024 (from national and international scientific databases), provided the opportunity for a synthesis of methodological practice and clinical perspective. The findings reveal a high prevalence of oral alterations in palliative patients, such as xerostomia, mucositis, dysphagia, orofacial pain, and opportunistic infections, with a direct association to vital activities crucial for feeding, communication, and social interaction. Basic dental interventions, performed humanely and continuously, have a remarkable impact on a significant number of aspects of patient comfort, well-being, and dignity, highlighting the importance of integrating the dentist into interdisciplinary care teams for palliative care. However, the literature points to significant gaps in professional training, still embedded in a classical biomedical view, which does not adequately address the complexity of end-of-life care. In summary, the integrative analysis thus outlines the need for formalized continuing education policies, the expansion of specific research in this area, and the integration of care practices focused on reducing suffering and improving quality of life. It is observed that Palliative Dentistry is necessary and expanding, where deeper theoretical understanding, technical-humanistic preparation, and institutional recognition are needed to achieve comprehensive, patient-centered, and ethically guided care among those at risk.